2010
DOI: 10.1002/jmri.22164
|View full text |Cite
|
Sign up to set email alerts
|

Modified brix model analysis of bone perfusion in subjects of varying bone mineral density

Abstract: Purpose: To apply pharmacokinetic modeling to the investigation of bone perfusion in subjects of varying bone mineral density. Materials and Methods:This study re-analyzed previous experimental data. A modified pharmacokinetic model was applied to data obtained from two prior studies of dynamic contrast-enhanced MR imaging of L3 vertebral body in 165 subjects (65 males, 100 females), classified into three groups (normal, osteopenia, and osteoporosis) according to bone mineral density. Three parameters, amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 30 publications
(53 reference statements)
4
28
0
Order By: Relevance
“…In addition, we compared these diffusion parameters with BMD and FF, and a positive correlation between D* and BMD was observed, which indicated a possible connection between bone marrow perfusion and BMD. This finding is supported by the results of previous studies in which the vertebral blood flow was decreased significantly in osteoporotic patients compared with that in healthy subjects [17,[20][21][22], thereby suggesting that the decrease in bone marrow perfusion may contribute to a decrease in the BMD and an increased risk of compression fracture. Although F is also a perfusionrelated parameter, we found no significant correlation between F and BMD.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, we compared these diffusion parameters with BMD and FF, and a positive correlation between D* and BMD was observed, which indicated a possible connection between bone marrow perfusion and BMD. This finding is supported by the results of previous studies in which the vertebral blood flow was decreased significantly in osteoporotic patients compared with that in healthy subjects [17,[20][21][22], thereby suggesting that the decrease in bone marrow perfusion may contribute to a decrease in the BMD and an increased risk of compression fracture. Although F is also a perfusionrelated parameter, we found no significant correlation between F and BMD.…”
Section: Discussionsupporting
confidence: 88%
“…First, we did not find a significant correlation between D* and FF because only a small number of healthy subjects with moderate BMD and FF were included in this study. However, previous studies have shown a negative correlation between the perfusion parameter and the FF in the bone marrow [20,21]. Therefore, we recommend that further evaluation in subjects with a wider range of BMD and FF, including osteopenia and osteoporosis, be undertaken with a lager sample size to confirm the findings in this study.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Additionally, the BM provides no direct measure of capillary permeability and is applicable only under specific permeability-limiting conditions [181]. However, the vasculature permeability can be roughly estimated with the product of the amplitude parameter, A Brix , and the rate constant, k ep [146,182].…”
Section: B the Brix Model (Bm)mentioning
confidence: 99%
“…The BM, which is particularly attractive since the AIF need not be known a priori [216], has been used to study the brain [146,170] and breast tumors [217][218][219][220]. It is frequently used to analyze the contrast uptake patterns in other applications, including intracranial meningiomas [221], malignant pleural mesothelioma [222], cervical cancer [223] and its chemoradiotherapy outcome [216], colorectal [224] and liver tumors [225], prostate diseases [180,[226][227][228][229], and recently, bone perfusion [182].…”
Section: Clinical Applications Of Parametric Modelsmentioning
confidence: 99%